Adverse drug reaction risk assessment with prescribed renal risk drugs among hospitalized patients attending a teaching hospital in South India - Sharma, Sadhna; Ramineni, Hari Babu; Shahitha, K. Poornima; Mounika, K.; Ramyachandra, P.; Girija, B. (International Journal of Research in Medical Sciences, 2020)
Background: Renal impairment is the primary cause of mortality and morbid conditions in patients. Inappropriate drug use in patients who are with risk of renal damage causes harmful and deleterious effects. Adjusting doses based on renal function is necessary for renal risk drugs, primarily to avoid adverse reactions of medications. Aim of the present study was to assess the risk of incidence on ADRs with drugs lowering the renal function. Methods: This is a cross-sectional observational study conducted in General Medicine department. 230 Patients constituted the sample in the study. The study was conducted for a period of one year and prescriptions with renal risk drugs were evaluated. Changes in the renal functional tests were compared to the normal range and adverse drug responses were monitored. Results: A total of 230 patients who fulfilled the inclusion criteria were included in the study. The meanage of the study subjects were 50.9±15.2 respectively. 56.39% patients were men and 43.6% were women. Renal risk drugs included in the study are anti-hypertensive, antibiotics, and analgesics. Paracetamol (24.77%) followed by telmisartan (20.85%) are the predominantly prescribed renal risk drugs with high incidence of adverse drug reactions. Causality assessment by Naranjo ADR probability scale showed out of 211 ADRs, 51.6% were possible, 25.59% were doubtful, 21.8% were probable and 0.94% was definite. Conclusions: The current study signifies that patients under high risk of renal damage require continuous monitoring and optimized therapy for better disease management.